Modeling a Service and Session Calculus with Hierarchical Graph Transformation - Bruni, Roberto; Corradini, Andrea; Montanari, Ugo (Electronic Communications of the EASST, 2010)
Graph transformation techniques have been applied successfully to the modelling of process calculi, for example for equipping them with a truly concurrent semantics. Recently, there has been an increasing interest towards hierarchical structures both at the level of graph-based models, in order to represent explicitly the interplay between linking and containment (like in Milner’s bigraphs), and at the level of process calculi, in order to deal with several logical notions of scoping (ambients, sessions and transactions, among others). In this paper we show how to encode a sophisticated calculus of services and nested sessions by exploiting a suitable flavour of hierarchical graphs. For the encoding of the processes of this calculus we benefit from a recently proposed algebra of graphs with nesting.